Studi Komparatif Visualisasi Render Konvensional Mahasiswa Desain Interior Universitas Pradita vs. AI Generatif - Sutapa , Widasapta; Putra, Bramanta Octa Danu; Izzati , Alifia Wida (KALBISCIENTIA Jurnal Sains dan Teknologi, 2025)
This study presents a comparative study on the quality of interior design visualization. It compares student work from Pradita University, which uses conventional software (3ds Max & SketchUp) with V-Ray and Enscape rendering engines, against results from generative artificial intelligence (AI) from various platforms. Using criteria such as efficiency, speed, visual quality, creativity, personalization, accuracy, ease of use, and limitations, this analysis highlights the strengths and weaknesses of each approach.The comparison shows that while AI excels in efficiency, speed, and ease of use for initial idea exploration, conventional software remains irreplaceable for personalization, technical accuracy, and the photorealistic visual quality needed for professional presentations. This study concludes that AI serves as a revolutionary complementary tool in the early stages of design, while conventional software is still the main instrument for precise and accurate final design.